2010
DOI: 10.1002/cyto.a.20943
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of intracellular and secreted cytokines via the generalized integrated mean fluorescence intensity

Abstract: The immune response in humans is usually assessed using immunogenicity assays to provide biomarkers as correlates of protection (CoP). Flow cytometry is the assay of choice to measure intracellular cytokine staining (ICS) of cell-mediated immune (CMI) biomarkers. For CMI analysis, the integrated mean fluorescence intensity (iMFI) was introduced as a metric to represent the total functional CMI response as a CoP. iMFI is computed by multiplying the relative frequency (percent positive) of cells expressing a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 12 publications
1
44
0
Order By: Relevance
“…Finally, we gated on the γΎ T cell receptor negative cells (which are presumably conventional αÎČ T cells) and further classified these into CD4+, CD8+, or other double negative (DN) cells. To determine the relative T cell subset contribution to IL-17A and IL-17F production, we used the integrated mean fluorescence intensity (iMFI) which is obtained by multiplying the number of cells expressing a particular marker with the mean fluorescence intensity in that channel (22). We found that γΎ T cells and CD4+ T H 17 cells are the predominant sources of IL-17A and IL-17F in the kidney and aorta, particularly following Ang II infusion (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we gated on the γΎ T cell receptor negative cells (which are presumably conventional αÎČ T cells) and further classified these into CD4+, CD8+, or other double negative (DN) cells. To determine the relative T cell subset contribution to IL-17A and IL-17F production, we used the integrated mean fluorescence intensity (iMFI) which is obtained by multiplying the number of cells expressing a particular marker with the mean fluorescence intensity in that channel (22). We found that γΎ T cells and CD4+ T H 17 cells are the predominant sources of IL-17A and IL-17F in the kidney and aorta, particularly following Ang II infusion (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
“…The specificity of the capture of plasma EVs with MNPs coupled to EVs-specific antibodies was demonstrated by comparison with MNPs coupled to non-specific control antibodies (Figure 3A,B). This specificity of capture is reflected in the integrated MFI (iMFI) 34,35 , which combines the relative amount of positive events with the mean fluorescence intensity of these events: 5574 and 70 for CD81, and 2074 and 22 for CD41 for specific staining and isotype control, respectively. Also, we used isotype control antibody to verify the specificity of detection of EV antigens (Figure 3D,F).…”
Section: Resultsmentioning
confidence: 99%
“…iMFI, which reports on the integrated fluorescence intensity by combining the relative amount of positive events with the mean fluorescence intensity (MFI) of these events 34,35 was calculated as suggested iMFI= (MFI) × (P); where P is the fraction of positive events.…”
Section: Methodsmentioning
confidence: 99%
“…For analysis, we used integrated MFI, which combines the metrics of frequency and MFI as a measure of total functional response 43,44 .…”
Section: Emsamentioning
confidence: 99%